If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -2y + y = 6 + -2x Combine like terms: -2y + y = -1y 4x + -1y = 6 + -2x Solving 4x + -1y = 6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 4x + 2x + -1y = 6 + -2x + 2x Combine like terms: 4x + 2x = 6x 6x + -1y = 6 + -2x + 2x Combine like terms: -2x + 2x = 0 6x + -1y = 6 + 0 6x + -1y = 6 Add 'y' to each side of the equation. 6x + -1y + y = 6 + y Combine like terms: -1y + y = 0 6x + 0 = 6 + y 6x = 6 + y Divide each side by '6'. x = 1 + 0.1666666667y Simplifying x = 1 + 0.1666666667y
| 20-1/4d=3/10d+16 | | 5t+3r+9t-10r-8= | | 1.4z-6=2.9z+9 | | 3x+5=-30 | | -29=11p | | (x-20)+(x-10)+40=360 | | v=bpk | | 6y+8=28 | | (x-20)+(x-19)+40=360 | | 10=6/7t+8 | | 3(y+8)+y=2(y+3)-4 | | 34-x/8=x/9 | | 12-6/5b=5 | | 1/4t+35/12=109/36 | | -4k-9=-1 | | -5z+7z=5z-3+8z | | 100=(16+r)+r | | 3[-5x+5-3(x+1)]=-7x-4 | | 2d=28 | | -4x+6y=-24 | | .25x+.05(20-x)=.10(6) | | -12/7/(-4/11) | | 3x+28=8 | | -5(y-4)=-4y-8 | | 2/3+7/8*9/2 | | 2-80/15 | | -1/4X+48=-2X+6 | | Y^2+y=5 | | -5z+5+6z=12 | | I=per | | x-3/13=5/13 | | p+p+2p+(-3p)-7=0 |